Structure-activity studies of bispyridinium antinicotinics to select candidates to treat soman intoxication as part of a combined therapy - Simon R. Turner; Christopher M. Timperley; Mike Bird; A. Christopher Green; Matthew E. Price; Helen Rice; John E. Chad; John E. H. Tattersall (PLoS ONE, 2025)
The standard treatment of atropine and oximes is insufficiently effective against all organophosphorus nerve agents. Bispyridinium non-oxime nicotinic antagonists are promising components to add to treatments. One of these, MB327, improves the survival of guinea-pigs after intoxication with tabun, sarin or soman. We extend our previous study of unsubstituted bispyridinium non-oximes with C1 to C10 alkane linkers to analogues having 4-tert-butylpyridinium rings and the same linker range. We report their effects on nicotinic-mediated calcium responses in muscle-derived (CN21) cells where nicotinic responses were inhibited in a concentration-dependent manner. A clear structure-activity relationship resulted: the inhibitory potency increased as the linker lengthened. Previous data showed the inhibition of human acetylcholinesterase in vitro increased similarly and that in general the toxicity to mice increased accordingly. However, the shorter analogues MB327 (4-tert-butyl C3) and MB442 (unsubstituted C5) compared favourably in toxicity to some oximes used to treat nerve agent poisoning. Like MB327, the non-oxime MB442, selected by the process described, improved the survival of guinea-pigs intoxicated with soman when combined with hyoscine and physostigmine or atropine and avizafone. Our research has now afforded two compounds able to protect guinea-pigs against nerve agent toxicity through a mechanism not previously exploited deliberately for this purpose.